Censorship - Caso, Frank (New York : Facts On File, 2008)
From the Publisher: Censorship is part of the Global Issues series, which is designed to be a first-stop resource for research on the key challenges facing the world today. Each volume contains three sections, beginning with an introduction that clearly defines the issue, followed by detailed case studies of the issue's impact in the United States and several other countries or regions. The second section draws together significant U.S. and international primary source documents, and the third section gathers useful research tools such as brief biographies, facts and figures, an annotated bibliography, and more. A foreword written by an expert in the field complements each volume. A chronology, glossary, and index provide additional help. Censorship suppresses human expression. It can be a means of limiting public dissension from an authoritarian and/or unpopular government; a method for protecting religious dogma from heresy, whether perceived or real; and a way of imposing a set of standards on communities or individuals. On the other hand, censorship, in the forms of film ratings, v-chips, and Internet filters, upholds parental authority. Thus, censorship is viewed both as evil and as a tool against evil. Even in the 21st century, with its emphasis on information and globalization, and with an electronic technology that disregards borders, censorship continues to dictate the lives of many. Providing a comprehensive overview of the different forms that censorship can take, this book examines the history and current practices of censorship in five countries-the United States, Russia, China, Zimbabwe, and Egypt-and discusses key counterstrategies. Parts II and III of the book include primary source documents relating to censorship in these five countries; biographical information on key figures whose lives were, or are, linked with censorship; and a list of U.S. and international organizations and agencies that monitor and publicize censorship activity, provide legal assistance, and develop counterstrategies. An annotated bibliography, a glossary, and a chronology complete this invaluable resource.
Includes bibliographical references p. 288-303 and index.
Keywords: Censorship -- Cross-cultural studies; Censorship -- Sources; Censorship -- United States -- Sources